BAURAN PEMASARAN (MARKETING MIX) KONVENSIONAL DAN DIGITAL DARI PEDAGANG PAKAIAN PASAR PONCOL JAKARTA PUSAT PADA MASA PANDEMI COVID-19 - Muhammad Ilham Nofitra (2023)
If reviewed from management marketing, traders in the market Poncol, Jakarta, when face Covid-19 pandemic, divided on two type, ie merchants do marketing in a manner traditional or conventional, and marketing digitally. Dotted reject from background behind such, research this aim for for know and analyze mix marketing conventional and digital from trader clothes Market Central Jakarta Poncol on period pandemic covid 19. Approach study qualitative with t technique data collection with interview depth, documentation, and observation. Technique data validation using method triangulation sources, techniques, and theory. Technique data analysis by procedural using interactive models from Miles et al (2016), includes data collection, data condensation, data presentation, and describe and verification conclusion. Technique data analysis by substantial use method comparison Among management marketing traditional with 7-P with management digital marketing with 4-C. Results study show that on marketing traditional or conventional looked own superiority in quality and variation product, price more cheap also finances from in terms of people and processes (such as free delivery to Jakarta area ). The downside from aspect location, access to market the more limited. So are promotions they still not yet maximum. Trader with management new digital marketing until can carry out creation product co-creation, however no activation level yet communal, currency and service level collaborative. Then superiority digital use by trader also from location, and process, which one convenience in digital use by consumer in have a look and carry out the buying process and payment. However the drawbacks is in price, promotion, and people or the person. That if want to in demand hard so must do good promotion and that can Secrete cost more, and from the person must own good creativity for draw inside use digital technology.